Poezja na usługach władzy – wczesna panegiryczna twórczość Symeona z Połocka - Kozak, Barbara (Studia Rossica Posnaniensia, 2011)
In this paper we endeavour to probe into the life and art of а unique poet and intellectual Symeon of Polotsk. We are dealing with this on the basis of his first still unpublished manuscript, focusing on the panegyrical works. Symeon, the future tutor of Peter the Great was formed in the turbulent times of the 17th century on the eastern lines of the weakening Polish empire. In his thirties he was forced to flee his native Polotsk and took refuge under the wings of tsar Alexei Mikhailovich in Moscow. There his talents found an excellent opportunity to flourish. The court of the Romanovs was Fast becoming the cultural and spiritual centre of the absolute monarchy, which was soon to become the powerful Russian empire. The poetry of Symeon took an indispensable part in the burgeoning royal ceremonial. In this the poet not only responded to the realities of the tsar’s court, but shaped new directions in the baroque art and influenced other wordsmiths of his time. The uniqueness of his approach to the panegyrical poetry employs biblical symbols and celestial analogies in order to celebrate the might and wisdom of his master and protector. This paper pays tribute to the indisputable originality of the works